2022
DOI: 10.1016/j.eclinm.2021.101261
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction improves lipid-related emerging cardiometabolic risk factors in healthy adults without obesity: Distinct influences of BMI and sex from CALERIE™ a multicentre, phase 2, randomised controlled trial

Abstract: Background For many cardiovascular risk factors there is no lower limit to which further reduction will result in decreased disease risk; this includes values within ranges considered normal for healthy adults. This seems to be true for new emerging metabolic risk factors identified by innovative technological advances. Further, there seems to be ever evolving evidence of differential responses to lifestyle interventions by sex and body compositions in the normal range. In this secondary analysis, we had the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In this context, a new question urgently needs to be addressed: what dietary patterns or lifestyles can provide the benefits of slowing aging for patients with cardiometabolic diseases? Calorie restriction is a typical example of a dietary pattern with anti-aging effects (76), which has been shown to reduce cardiometabolic risk by clinical evidence from substantial randomized controlled studies (77,78). Our study suggested that dietary inflammatory potential is a key concern and consideration in developing dietary patterns for patients with cardiometabolic disease, especially among CVD and hypertension patients.…”
Section: Discussionmentioning
confidence: 70%
“…In this context, a new question urgently needs to be addressed: what dietary patterns or lifestyles can provide the benefits of slowing aging for patients with cardiometabolic diseases? Calorie restriction is a typical example of a dietary pattern with anti-aging effects (76), which has been shown to reduce cardiometabolic risk by clinical evidence from substantial randomized controlled studies (77,78). Our study suggested that dietary inflammatory potential is a key concern and consideration in developing dietary patterns for patients with cardiometabolic disease, especially among CVD and hypertension patients.…”
Section: Discussionmentioning
confidence: 70%
“…High-mannose (M5–M9) glycans in human plasma proteins are predominantly derived from the apolipoprotein B-100 (ApoB) and immunoglobulin M (IgM) [ 33 ]. ApoB transports most of the plasma cholesterol and has a major role in the assembly of atherogenic low- and very low-density lipoproteins [ 33 ], and it has been shown that its concentration decreases during calorie restriction [ 71 ]. Yet, due to the analytical method used for plasma N-glycan analysis, it is hard to say whether the reduction in total plasma protein high-mannose glycans after LCD is solely caused by the change in ApoB concentrations or by the changes in ApoB glycosylation, or both.…”
Section: Discussionmentioning
confidence: 99%
“…ApoB and LDL particle (LDL-P) were measured from frozen serum (Y2) and EDTA plasma (Y7, Y15, Y20, and Y30) samples by NMR spectroscopy at Labcorp (Morrisville, NC) using the high-throughput Vantera® Clinical NMR Analyzer platform. ApoB was quantified using partial least squares regression modeling of the lipid methyl and methylene spectral region as previously described ( 18 ). ApoB concentrations produced by this assay have been extensively validated as equivalent to those measured by immunoassay ( R = 0.98), with precision and accuracy verified quarterly by blinded Centers for Disease Control and Prevention Lipids Standardization Program proficiency testing ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…ApoB was quantified using partial least squares regression modeling of the lipid methyl and methylene spectral region as previously described ( 18 ). ApoB concentrations produced by this assay have been extensively validated as equivalent to those measured by immunoassay ( R = 0.98), with precision and accuracy verified quarterly by blinded Centers for Disease Control and Prevention Lipids Standardization Program proficiency testing ( 18 ). LDL-P was quantified by NMR LipoProfile ® analysis using the LP4 deconvolution algorithm ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%